Impact of differential torsional rotor cant on the flight characteristics of a passenger-grade quadrotor - Atci, K.; Jusko, T.; Strbac, A.; Guner, F. (My University, 2022)
At the Institute of Flight Systems at DLR, studies have been performed to understand the flight characteristics of novel eVTOL configurations. As part of these studies, previously conducted handling qualities assessments on a 2-passenger quadrotor configuration had revealed major deficiencies about its yaw axis. Based on this result, the quadrotor model has been modified by differential torsional canting to improve its yaw characteristics. This paper analyzes the resulting impacts of such modification on the flight performance, dynamic stability and handling qualities. A piloted virtual flight test campaign was conducted to assess predicted and assigned handling qualities levels in compliance with the quantitative and qualitative performance standards of ADS-33E. The results show an improvement in midterm yaw response at the expense of increase in total required power. The pilot ratings and comments also confirm the improvement on the yaw response upon the flown MTEs.